Carotid artery stenting before surgery for carotid artery occlusion associated with acute type A aortic dissection: Two case reports. Issue 6 (December 2020) - Funakoshi, Yusuke; Imamura, Hirotoshi; Tokunaga, So; Murakami, Yasutaka; Tani, Shoichi; Adachi, Hidemitsu; Ohara, Nobuyuki; Kono, Tomoyuki; Fukumitsu, Ryu; Sunohara, Tadashi; Omura, Yoshihiro; Matsui, Yuichi; et al.
Background: We experienced two cases of ischemic stroke resulting from carotid artery occlusion associated with acute type A aortic dissection (ATAAD), in which carotid artery stenting before the surgery for ATAAD resulted in good clinical outcomes. Case 1 description: A 63-year-old woman was hospitalized for conscious disturbance, right hemiparesis, and total aphasia. Computed tomography of the head showed no abnormal findings. Computed tomography angiography showed ATAAD and bilateral common carotid artery occlusion. Surgery was not indicated for ATAAD because of a poor prognosis of ischemic stroke. However, carotid artery stenting of the left common carotid artery occlusion was successfully performed, and her neurological findings improved. The patient underwent hemiarch replacement for ATAAD on the day after carotid artery stenting. Her final modified Rankin Scale was 1.Case 2 Description: A 57-year-old woman was hospitalized for mild left hemiparesis. Magnetic resonance imaging showed right watershed infarction and right common carotid artery occlusion. Computed tomography angiography showed ATAAD. After hospitalization, conscious disturbance appeared and left hemiparesis worsened. Ischemic stroke indicated a poor prognosis for revascularization by surgery for ATAAD. Thus, carotid artery stenting of the right common carotid artery occlusion was performed. The patient's neurological findings improved and she underwent hemiarch replacement for ATAAD at 19 days after carotid artery stenting. Her final modified Rankin Scale was 1. Conclusions: In the present cases, although ischemic stroke was serious and precluded surgical indication for ATAAD, carotid artery stenting before surgery for ATAAD resulted in good clinical outcomes. Performing carotid artery stenting before surgery for ATAAD is challenging but achievable, and is a valid treatment option depending on the individual cases.